Some indicators of Galshar red goat's cashmere quality - N, Bayarmaa; B, Narantuya (Mongolian Journal of Agricultural Sciences, 2018)
For the purpose of the studying soft wool quality of goat from Khentii aimag, Galshar soum were determined its percentage in all wool, length and diameter. Average amount of percentage of soft wool at shoulder blade and thigh were 48.68±0.53% (18.16-64.80%) and 85.84±0.55% (60.51-96.47%), length and diameter of soft wool in average and at shoulder blade and thigh 4.23±0.04 cm (2.87-5.87 cm), 4.24±0.04 cm (3.03-5.87 cm), 15.08±0.02μM (13.5-17.4μm) 15.04±0.03 mkm (13.5-17.3μm), 15.12±0.02μm (13.7-17.4μm) correspondly.